Cysticercosis and epilepsy in rural Tanzania: a community‐based case–control and imaging study. Issue 9 (26th May 2015) - Hunter, Ewan; Burton, Kathryn; Iqbal, Ahmed; Birchall, Daniel; Jackson, Margaret; Rogathe, Jane; Jusabani, Ahmed; Gray, William; Aris, Eric; Kamuyu, Gathoni; Wilkins, Patricia P.; Newton, Charles R.; et al.
Abstract Objective To assess the contribution of neurocysticercosis (NCC) to the burden of epilepsy in a rural Tanzanian population. Methods We identified adult people with epilepsy (PWE) in a door‐to‐door study in an established demographic surveillance site. PWE and community controls were tested for antibodies to Taenia solium, the causative agent of NCC, and all PWE were offered a computed tomography (CT) head scan. Data on household occupancy and sanitation, pig‐keeping and pork consumption were collected from PWE and controls and associations with epilepsy were assessed using chi‐square or Fisher's exact tests. Results Six of 218 PWE had antibodies to T. solium (2.8%; 95% CI 0.6–4.9), compared to none of 174 controls (Fisher's exact test, P = 0.04). Lesions compatible with NCC were seen in eight of 200 CT scans (4.0%; 95% CI 1.3–6.7). A total of 176 PWE had both investigations of whom two had positive serology along with NCC‐compatible lesions on CT (1.1%; 95% 0.3–4.0). No associations between epilepsy and any risk factors for NCC were identified. Conclusions Neurocysticercosis is present in this population but at a lower prevalence than elsewhere in Tanzania and sub‐Saharan Africa. Insights from low‐prevalence areas may inform public health interventions designed to reduce the burden of preventable epilepsy.